PENGARUH MEDIA PROMOSI KESEHATAN TERHADAP PENGETAHUAN CUCI TANGAN PAKAI SABUN DI SDN III GUNUNGJATI JABUNG KABUPATEN MALANG - Dimas Dwi Yoga Saputra (Jurnal Informasi Kesehatan Indonesia (JIKI), 2022)
Background: Hand hygiene can reduce the risk of hand disease transmission and person-to-person infection. The purpose of this study was to determine the effect of kahoot learning media on knowledge about hand washing with soap in 5th graders at SDN III Gunungjati in Jabung District, Malang Regency. Subjects and Method: This research uses quantitative research, pre-experimental research design with one-group pre-test-post-test approach. The population in this study were all 5th grade students of SDN III Gunungjati, totaling 22 students. Sampling was carried out using a total sampling Results: In the bivariate analysis with the Wilcoxon test to determine the effect of Kahoot learning media on increasing knowledge. Obtaining the results of knowledge before being given treatment were 18 students (81.8%) with good criteria 2 students (9.1%) with sufficient criteria and 2 students (9.1%) with less criteria, meanwhile after being given treatment in the form of kahoot learning media about hand washing with soap the number of students who have sufficient and less criteria has increased with the result that 22 (100%) students all good results. Conclusion: Based on the results of this study, the kahoot learning media is effective for increasing knowledge about hand washing with soap in 5th grade students at SDN III Gunungjati, Jabung District, Malang Regency. Keywords: Handwashing, Education, Games, Kahoot.